2023
DOI: 10.3390/jcdd10070281
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Access Aortic Valve Surgery

Abstract: Minimally invasive approaches to the aortic valve have been described since 1993, with great hopes that they would become universal and facilitate day-case cardiac surgery. The literature has shown that these procedures can be undertaken with equivalent mortality rates, similar operative times, comparable costs, and some benefits regarding hospital length of stay. The competing efforts of transcatheter aortic valve implantation for these same outcomes have provided an excellent range of treatment options for p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Aortic valve (AV) surgery has evolved towards less invasive approaches including mini-sternotomy or right thoracotomy ( 89 ). Several studies have shown that patients undergoing less invasive AV surgery have a shorter hospital stay, less pain, shorter duration of ventilation, less blood loss, and less blood transfusion than patients undergoing conventional full sternotomy ( 90 ).…”
Section: Intraoperative Choices For Frail Patients: the Right Strateg...mentioning
confidence: 99%
“…Aortic valve (AV) surgery has evolved towards less invasive approaches including mini-sternotomy or right thoracotomy ( 89 ). Several studies have shown that patients undergoing less invasive AV surgery have a shorter hospital stay, less pain, shorter duration of ventilation, less blood loss, and less blood transfusion than patients undergoing conventional full sternotomy ( 90 ).…”
Section: Intraoperative Choices For Frail Patients: the Right Strateg...mentioning
confidence: 99%